IDOSOS REMANESCENTES DE QUILOMBO DO MUNICÍPIO DE ALCÂNTARA-MA - Silva, Cleidson de Morais (2013)
Introduction: Population aging is a global phenomenon, recognized as demand generator and a great political challenge for all countries, including Brazil. Living longer is a common aspiration, yet it is needed to add quality of life to the added years. Inasmuch black population, specially Quilombola communities, is known by its social and healthy vulnerabilities, it becomes relevant to investigate the construct quality of life in this doubly vulnerable population segment.Objectives: To assess quality of life of Quilombo s remnant older adults from Alcântara- MA, through domains: physical, psychological, social relationships and environment. Describe their socioeconomic and demographic profile.Methodology: That s an analytical, observational, cross-sectional study with quantitative approach in a sample(n=129) divided into three groups. Convenience sampling was adopted, data was collected among June and December, 2012. The data collection instruments were a socio-demographic questionnaire and WHOQOL-BREF Portuguese version. Statistical analysis was performed by SPSS 20 program, being calculated descriptive statistics, analysis of variance one way, Bonferroni s test, bivariate analysis- Pearson s and Spearmann s correlation. Results: The best perception of quality of life and health was observed in the Group III, significant correlations were found between marital status and quality of life in the Group III, trash destination and quality of life, number of children and health perception, both in the Group II. The analysis of variance revealed that Psychological Domain for Group I was statistically lower, this result was confirmed through Bonferrni s test, whereas regular, positive correlations were observed among overall facets Quality of Life and Health( Group I) and among Quality of Life and Health with Environment Domain(group III). Final Remarks:The findings suggest the adoption of health actions for healthy aging promotion, creation of opportunities for leisure activities and combating depression symptoms, the need for health actions planning for elderly and adoption of measures of environment sanitation.